Electronic participation third IFIP WG 8.5 international conference, ePart 2011, Delft, The Netherlands, August 29-September 1, 2011. proceedings - Tambouris, Efthimios; Macintosh, Ann; Bruijn, Hans (Lecture notes in computer science, 2011)
This book constitutes the refereed proceedings of the Third International Conference on Electronic Participation, ePart 2011, held in Delft, The Netherlands, in August/September 2011. The 26 revised full papers were carefully reviewed and selected from numerous submissions. The papers are organized in topical sections on appreciation of social media; visualizing arguments; understanding eParticipation; eParticipation initiatiaves and country studies; participation and eServices; and innovative technologies.